2009
DOI: 10.1021/la901109e
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin and Integrin Regulation of Epithelial Cell Migration

Abstract: These studies quantified the relative effects of E-cadherin expression and homophilic ligation on the integrin-mediated motility of epithelial cells. Micropatterned proteins were used to quantitatively titrate the ligation of E-cadherin and integrin receptors, in order to assess their coordinate influence on the migration velocities of MDA-MB-231 breast tumor epithelial cells. Fibronectin, E-cadherin, and mixtures of fibronectin and E-cadherin were covalently patterned on solid surfaces at defined compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Functionalised surfaces for the controlled presentation of proteins have been widely used to study fundamental biology, including adhesion and migration (Charnley et al, 2012;Gavard et al, 2004;Kovacs et al, 2002;Silvestre et al, 2009), division (Charnley et al, 2013;den Elzen et al, 2009;Toyoshima et al, 2007), immune responses (Charnley et al, 2009;Grakoui et al, 1999;Manz et al, 2010;Mossman et al, 2005) and T cell development (Dallas et al, 2005;Janas et al, 2010;Tussiwand et al, 2011). Here, we demonstrated that these surfaces successfully mimicked another aspect of T cell development; developing T cells cultured on the surfaces underwent ACD and this process was coordinated by external cues and restricted to the DN3a stage of development.…”
Section: Discussionmentioning
confidence: 58%
“…Functionalised surfaces for the controlled presentation of proteins have been widely used to study fundamental biology, including adhesion and migration (Charnley et al, 2012;Gavard et al, 2004;Kovacs et al, 2002;Silvestre et al, 2009), division (Charnley et al, 2013;den Elzen et al, 2009;Toyoshima et al, 2007), immune responses (Charnley et al, 2009;Grakoui et al, 1999;Manz et al, 2010;Mossman et al, 2005) and T cell development (Dallas et al, 2005;Janas et al, 2010;Tussiwand et al, 2011). Here, we demonstrated that these surfaces successfully mimicked another aspect of T cell development; developing T cells cultured on the surfaces underwent ACD and this process was coordinated by external cues and restricted to the DN3a stage of development.…”
Section: Discussionmentioning
confidence: 58%
“…Nanotechnology may help understand ovarian cancer cell adhesions by using specific surface topographies that have nanoscale features or certain functional groups in order to evaluate interactions of ovarian cancer cells or ovarian CSCs with these surfaces, which may be designed to simulate mesothelial cells. For example, such surfaces that had immobilized E-cadherin or fibronectin on substrates have been used with other cell types [35], and they could easily be used with ovarian cancer cells. The value of this is to create simplified models with isolated molecules to understand interaction events that usually lead to adhesion of ovarian cancer cells to the mesothelial lining of the peritoneum, which precedes their invasion and metastasis.…”
Section: Other Possibilitiesmentioning
confidence: 99%
“…Microfluidic platforms, and more recently photolithography approaches, have long been used to create spatial gradients of tethered and soluble biomolecules on 2D substrates . Resultant studies employing these gradients have been used to examine a wide range of cellular processes such as motility and polarity . Polyacrylamide substrates containing gradients in elastic modulus have also recently been used to study the impact of stiffness gradients on mesenchymal stem cell behavior .…”
Section: Introductionmentioning
confidence: 99%